(untitled) (Texas Journal of Philology, Culture and History, 2024)
This study delves into the critical role of education leadership and management (ELM) in preparing undergraduate students for future success. By examining the theoretical underpinnings and practical applications of ELM, this research highlights its significance in fostering essential leadership, management, and problem-solving skills. Through a comprehensive analysis of the literature and realworld examples, this study underscores the importance of integrating ELM into undergraduate curricula to cultivate well-rounded graduates who are equipped to address complex challenges and drive positive change in diverse organizational settings.